Integrated climate, ecological and socioeconomic scenarios for the whale watching sector - Sousa, Andreia G. (2022)
Unprecedented human induced changes to the climate system have already contributed to a variety of observed impacts to both ecosystems and populations. Decision-makers demand impact assessments at the regional-to-local scale to be able to plan and define effective climate action measures. Integrated socio-ecological assessments that properly consider system uncertainties require the use of prospective scenarios that project potential climate impacts, while accounting for sectoral exposure and adaptive capacity. Here we provide an integrated assessment of climate change to the whale watching sector by: 1) extending the European Shared Socio-economic Pathways (Eur-SSPs) and developing four whale watching SSP narratives (WW-SSPs) and 2) characterize each key element comprised in the WW-SSPs for the time period 2025–2055. We applied this approach in a case study for the Macaronesia region where we developed scenarios which integrate the socio-economic (WW-SSPs), climate (RCPs) and ecological (species' thermal suitability responses) dimensions of whale watching. These scenarios were used by local stakeholders to identify the level of preparedness of the whale watching sector. When confronted with scenarios that combine this ecological dimension with projected climate changes and the four different socioeconomic narratives, stakeholders assessed the whale watching sector in Macaronesia as being somewhat prepared for a Sustainable World and a Fossil Fuel Development World, but somewhat unprepared for a Rivalry World. No consensus was reached regarding the sector's preparedness level under an Inequality World scenario. Our study demonstrates the importance of considering multiple dimensions when assessing the potential challenges posed by climate change and provides a needed resource to help the whale watching sector in Macaronesia, and elsewhere, in its effort to devise efficient climate action policies and strategies.